PENGARUH LATIHAN POGO JUMP TERHADAP DAYA LEDAK OTOT TUNGKAI PADA TIM VOLI PUTRA PUMA KABUPATEN PELALAWAN - Tulus Prionggo; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is the lack of explosive power of leg muscle during smash and block on male volleyball team of Puma Pelalawan Regency. Based on these problems the writer gives the form of pogo jump exercises. This study was conducted to know how much the influence of pogo jump exercises on the explosive power of leg muscles on the male volleyball team of Puma, so that when doing the jump smash and block the player will get maximum jump results. This type of research is a experimental research with design one group pretest-posttest design research. The population in this study is male volleyball team of Puma which amounted to 12 people. While the sampling technique used is total sampling, where the entire population of 12 people used as sample. With vertical jump test instrument then descriptive analysis and normality test using liliefors test at significant level α (0.05) the average result of pretest vertical jump is 46. Furthermore, by giving the pogo jump exercise for 16 times on the volleyball team which amounted to 12 people, Then the posttest vertical jump generates to average of 54,5. Based on the results of pretest and posttest data analysis there is a difference in numbers that increased by 8,5. From t test analysis yield Thitung equal to 6,58 and Ttabel equal to 1,796 mean thitung > ttabel. It can be concluded that pogo jump exercises affect the results of explosive power of leg muscle on the male volleyball team of Puma.Keywords: Pogo Jump, The Explosive Power Of Leg Muscle